2021
DOI: 10.1016/j.jtocrr.2021.100254
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Specific Association of Statin Use and Reduced Risk of Recurrence of Early Stage NSCLC

Abstract: Introduction Statins, used for their lipid-lowering activity, have anti-inflammatory and anticancer properties as well. We evaluated this potential benefit of statin use in patients with NSCLC. Methods All 613 patients with pathologic stage 1 or 2 NSCLC who had lobectomy without neoadjuvant therapy at our institution during 2008 to 2015 were included. Association between presurgery statin use and overall survival and recurrence-free survival (RFS) was analyzed using Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Obesity as a confounder was reported in a study from our institution which demonstrated a survival benefit in use of the antidiabetic drug metformin in NSCLC, but only in patients who were overweight or obese 25 . Recently published data from our institution has also demonstrated a survival benefit with statins in NSCLC, but only in patients with BMI ≥ 30 24 …”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Obesity as a confounder was reported in a study from our institution which demonstrated a survival benefit in use of the antidiabetic drug metformin in NSCLC, but only in patients who were overweight or obese 25 . Recently published data from our institution has also demonstrated a survival benefit with statins in NSCLC, but only in patients with BMI ≥ 30 24 …”
Section: Discussionmentioning
confidence: 83%
“…25 Recently published data from our institution has also demonstrated a survival benefit with statins in NSCLC, but only in patients with BMI ≥ 30. 24 There are multiple proposed mechanisms for the antitumor effects of statins. Antiproliferative effects mediated by blocking the transition of G1-S in the cell cycle, apoptosis induction via products of the mevalonate pathway, inhibition of angiogenesis, and inhibition of cell signaling pathways associated with invasion and metastases have been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients who are overweight or obese, statin use was associated with improved recurrence-free survival [161]. These higher-BMI patients who used statin were found to have higher expression of granzyme A and interferon-γ, which are tumoricidal [161].…”
Section: Statinsmentioning
confidence: 99%